Efektivitas Daun Murbei Sebagai Pengganti Konsentrat dalam Sistem Rumen in Vitro - S Syahrir; K G Wiryawan; A Parakkasi; M Winugroho; O.N P Sari (Media Peternakan, 2009)
Mulberry leave has a great potential as animal feed because of its high nutrient content. It also has deoxynojirimycin (DNJ) compound, that is potential to increase fermentability of fibrous feed in ruminal system. An in vitro experiment was conducted to investigate the capability of mulberry leaves to substitute concentrate as feed for ruminant in increasing fermentability of fibrous feed in ruminal system. This experiment was carried out using randomized block design with five treatments and four replications. The treatments were: P0 (50% rice straw + 50% concentrate) as a control, P1 (50% rice straw + 37.5% concentrate + 12.5% mulberry leave), P2 (50% rice straw + 25% concentrate + 25% mulberry leave), P3 (50% rice straw + 12.5% concentrate + 37.5% mulberry leave), P4 (50% rice straw + 50% mulberry leave). Variables measured were fermentability (NH3 and VFA concentrations), pH, gas production, dry matter and organic matter digestibility. Data were analyzed using analysis of variance and duncan multiple range test was further used to test the significant differences. VFA concentration, dry matter digestibility and organic matter digestibility were significantly difference (P < 0.05) among treatments. However, there was no significant effect on the other variables. It is concluded that mulberry leave are able to substitute the concentrate and increased fermentability of fibrous feed in ruminal system. Key words: mulberry leave, rice straw, ruminal fermentation, in vitro